Market access and firm performance: Evidence based on GIS analysis of road network and manufacturing-plant-level data from India - Somnath Sharma; Shashi Kant; Ranjeeta Mishra; Dina Azhgaliyeva (Asian Development Bank Institute (ADBI), 2022)
This paper investigates whether better access to markets through an improved road network plays a role in improving the profitability of firms in India. We construct a district-level market access index using Indian road network shapefiles, district boundaries, and nightlight raster images and estimate the shortest driving distances for districts using the road network. Using the annual survey of industries data for India during the period 2001-2015, we show that market access through improved road connectivity resulted in a lower dispersion of ROA between 2001 and 2015 in India.
Keywords: D22; D24; H54; 330; India; road infrastructure; firm productivity; market access index; electricity deficit; road length